The Effects of COVID-19 on the Placenta During Pregnancy - Rad, Habib Sadeghi; Röhl, Joan; Stylianou, Nataly; Allenby, Mark C.; Bazaz, Sajad Razavi; Warkiani, Majid E.; Guimaraes, Fernando S. F.; Clifton, Vicki L.; Kulasinghe, Arutha (Frontiers in Immunology, 2021)
COVID-19 has caused a global pandemic, caused by the severe acute respiratory syndrome coronavirus 2, SARS-CoV-2. The virus primarily affects the lungs where it induces respiratory distress syndrome ranging from mild to acute, however, there is a growing body of evidence supporting its negative effects on other system organs that also carry the ACE-2 receptor, such as the placenta. The majority of newborns delivered from SARS-CoV-2 positive mothers test negative following delivery, suggesting that there are protective mechanisms within the placenta. There appears to be a higher incidence of pregnancy-related complications in SARS-CoV-2 positive mothers, such as miscarriage, restricted fetal growth, or still-birth. In this review, we discuss the pathobiology of COVID-19 maternal infection and the potential adverse effects associated with viral infection, and the possibility of transplacental transmission.